Perbandingan Akurasi dan Efisiensi antara Survei dengan Kerangka Complete listing dan Mapping - M Irfan Zulfahmi; Achmad Prasetyo (Seminar Nasional Official Statistics, 2021)
Data collection activities through large-scale surveys are often faced with constraints of time, effort, and operational costs, especially if the data to be collected is urgent. One way to overcome this is to use a rapid survey. However, the rapid survey uses a mapping sample frame which does not contain all observation units, resulting in a coverage error that affects the estimated value. Therefore, the researcher aims to determine the coverage error and bias values observed and then compare the accuracy and efficiency of the rapid survey and conventional survey. The research’s stage are development sampling frame, simulation, indicator calculation, RMSE comparison, and efficiency analysis. The estimation’s results in the mapping frame is underestimated and has lower accuracy than conventional survey. Rapid survey are more efficient when fix RMSE and no more efficient than conventional survey when fix time.